EFEKTIVITAS METODE RESITASI TERHADAP KEMAMPUAN MENGANALISIS UNSUR INTRINSIK CERITA RAKYAT BATU BADAONG DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS VII MTS NURUL HUDA LIMBORO KAB. SERAM BAGIAN BARAT - Muslim Muslim; Gimin Jimani; La Ode Yedin; Septiliana Septiliana (Lembaga Penelitian dan Pengabdian Masyarakat FKIP UMB, 2020)
The goal to be achieved in this study is to describe objectively the effectiveness of the recitation method on the ability to analyze the intrinsic elements of the Batu Badaong folklore in Indonesian Language Learning in Class VII students of MTs Nurul Huda Limboro Kab. West Seram. This research method is descriptive quantitative and this research is classified as experimental research with one group pretest-posttest research design. The population in this study were all seventh grade students at Mts Nurul Huda Limboro in the 2019-2020 school year. The sample in this study was 73 students, consisting of two classes. The instrument of this research is a test of the intrinsic elements of folklore. The number of test items is 8 objective questions. The data collection technique of this research is a test technique. That is, the researcher distributes questions to each sample student. The data analysis technique used descriptive statistics. The recitation method used in this study was considered effective because it was able to increase student learning outcomes with a significant gain from 41% to 86%. And reached a ratio of 70 according to the standard of effectiveness according to the Ministry of Home Affairs Research and Development reference.